Perkembangan Teknologi Digital dan Edukasi Hukum untuk Meningkatkan Perlindungan Konsumen Digital terhadap Penipuan Online di Indonesia - Donny Setha (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of digital technology has brought about significant changes in people's transaction patterns, particularly with the increasing use of online platforms for buying and selling. This phenomenon provides convenience for consumers and merchants, but is also accompanied by a high rate of online fraud experienced by both consumers and merchants. This fraud can take the form of fraudulent transactions, goods not received, or identity fraud. Low public legal literacy regarding rights and obligations in digital transactions is one of the main causes of weak legal protection for fraud victims. Many consumers and merchants are unaware of their rights and the legal procedures to take when experiencing fraud. This community service activity aims to increase the legal understanding of the public, especially online merchants and consumers, regarding digital consumer protection and legal fraud handling mechanisms. The activity implementation methods included interactive legal counseling, distribution of closed-ended questionnaires, case study simulations, Q&A discussions on legal issues, and light consultations. A total of 60 respondents, consisting of 30 merchants and 30 consumers, participated in the closed-ended questionnaire. The results showed that the majority of participants did not fully understand their rights in digital transactions and were unaware of the legal procedures to take when experiencing fraud. Despite this, participant interest in legal education was very high, with over 75% stating they wanted further legal assistance. This activity is expected to provide the public with better insight into their rights and obligations in digital transactions, as well as raise awareness of the importance of legal protection in the digital age. This is expected to make the public more vigilant and protected from potential online fraud in the future. Furthermore, increased legal literacy is expected to create a safer and more trustworthy digital transaction ecosystem for all parties.